Students’ Perceptions toward Health Science Career Choice: A Case from Cambodia - Sorn, Virak (Journal of Education and Practice, 2023)
Purpose: The purpose of this study is to investigate the students' perception of choosing a health science major as a career choice for their higher education degree, to understand why and what motivates them, and to contextualize how these views would have an impact on their studies. Methodology: This study was a mixed-methods study consisting of quantitative and qualitative data. Quantitative data were collected using an anonymous Google-form questionnaire, and FGD was used to collect qualitative data. Quantitative data were analyzed using Statistical Package for the Social Sciences (SPSS) version 24, while qualitative data were analyzed thematically. Findings: The findings categorized the students' choice of a health science major based on their personal life experiences, role modules, family support, engagement, high school performance, and career viewpoints. Thus, results indicated that students' enrollment in a health science major as a career choice was due to their interests in future career perspectives, academic performance, and life experience, with the support and encouragement of their families. Unique Contribution to Theory, Practice and Policy: In conclusion, several factors motivate students to consider a health science major for future improvement and to maintain the quality of healthcare experts in Cambodia. Those factors, including life experience, role modules, career interest, academic performance, family direction, and accessibility of health science information, significantly impact students' decisions to pursue a HE degree. This study's findings are essential information that will help prepare students for health science majors and inform parents, health science universities, and governance to plan for providing support and inspiration to students since high school for this major of study.